Reforming of Ethanol to Produce Hydrogen Over PtRu/CeO2 Catalyst - Chiou, Josh Y.Z; Bi, Jia-Lin; Kung, Hsuan-Ying; Wang, Chen-Bin (International Journal of Chemistry and Materials Research, 2015)
The aim of this study is focused on the design of ethanol reforming catalyst to produce hydrogen at low-temperature with high ethanol conversion (XEtOH), hydrogen yield (YH2) and low CO distribution. A highly dispersed PtRu/CeO2 catalyst is prepared by impregnation method. Catalytic performance and products distribution toward ethanol reforming reactions is evaluated in a fixed bed reactor. Three processes of ethanol reforming are performed: steam reforming of ethanol (SRE), partial oxidation of ethanol (POE) and oxidative steam reforming of ethanol (OSRE). The results show that the SRE reaction requires high temperature (T > 500 C) to achieve complete ethanol conversion, however, low temperature for both POE and OSRE (T < 300 C) reactions. Analytical results indicate the optimized molar ratios of O2/EtOH and H2O/EtOH are 0.44 and 4.9, respectively. Under this condition, the OSRE reaction over PtRu/CeO2 catalyst is completely converted around 340 C to get 2.3% CO and 4.1 mol H2/mol EtOH.